MATRIX STRUCTURE FOR MANAGEMENT OF THE ACTIVITIES OF STUDENTS’ RESEARCH GROUPS - M. N. Yelunin; Semen A. Piyavsky (Высшее образование в России)
This paper describes an information technology (matrix structure) that enables to generate mixed students’ research groups. The pivot of the matrix structure is the interdisciplinary course “The technology of vocational activities”. Student’s research work consists of two parts: an individual task and participation in teamwork under the guidance of a team leader, so that his work is closely connected with the leading research areas of the department.